A Semantic Analysis of Sentences, Utterances, and Presuppositions in the Short Story "Rules of the Game" by Amy Tan - Brian Adam Anggareksa; Muhamad Rizal Saputra; Muhammad Fikri Alfarizi; Rafael Raka Kristomeo; Rezaldy Reyhan Putra (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aimed to examine how sentences, utterances, and presuppositions interact in Amy Tan’s short story “Rules of the Game.” This paper analyzed twenty of data to uncover patterns in structure and meaning. Each data point was categorized by sentence types such as simple sentence, compound sentence, or complex sentence, utterance function such as declarative, interrogative, or imperative, and presupposition category such as existential, structural, or lexical. The results showed that compound and complex sentences added depth to the narrative, utterances revealed interpersonal dynamics, and presuppositions uncovered shared cultural expectations. These findings highlighted how linguistic forms shape deeper meanings, offering new insight into themes of identity, tradition, and generational conflict.